GAMIFICATION OF A DIGITAL SNAKE AND LADDER GAME BASED ON LIFE SCORE FOR ADOLESCENT TUBERCULOSIS EDUCATION - Hani Dewi Ariessanti; Jefry Sunupurwa Asri; Ryan Putra Laksana; Dwi Sloria Suharti; Muhammad Thifaal Dzaki; Muhammad Fikri (RADJA PUBLIKA, 2026)
Tuberculosis (TB) remains a public health problem in Indonesia, particularly among adolescents with relatively low health literacy and limited access to engaging educational media. Conventional educational approaches tend to be less effective in increasing adolescent engagement and understanding of TB prevention and spread behaviors. This study aims to design and implement a gamification-based digital snakes and ladders game as a TB education medium for adolescents by integrating a life score algorithm to represent user health behaviors. The research method used is research and development with the stages of needs analysis, system and gamification design, prototype development, and initial testing. The game was developed using web-based technology with active and passive box mechanisms containing TB educational content, as well as a reward and penalty system using ladders and snakes. The results showed that the game prototype was successfully implemented according to the design, where the life score algorithm was able to dynamically depict changes in healthy and risky behaviors during the game. The integration of gamification elements also allows for the delivery of TB educational materials interactively and contextually. This study concludes that the gamification-based digital snakes and ladders game has the potential to be an effective alternative educational medium in increasing adolescents' understanding of TB prevention and spread.